PHARMACO-METABOLOMICS OF BLOOD PRESSURE RESPONSE TO BETA-BLOCKERS AND DIURETICS. (June 2018) - Campbell, D.; Aman, A.; Iniesta, R.; Menni, C.; Gong, Y.; Cooper-DeHoff, R.; Johnson, J.; Burgess, K.; Barrett, M.; Lewis, C.; Chowienczyk, P.; Padmanabhan, S.
Abstract: Objective: Pharmacometabolomics have shown promise in identifying small molecule markers for drug response. In the current study, we propose to identify pre-treatment metabolomic markers of anti-hypertensive drug response in two multi-ethnic RCTs of mono-therapy with hydrochlorothiazide, atenolol, metoprolol, and chlorthalidone. Design and method: The PEAR (Pharmacogenomic Evaluation of Antihypertensive Responses) and PEAR 2 studies were prospective, multi-centre studies of two anti-hypertensive drugs in subjects with uncomplicated mild to moderate essential hypertension. Subjects were randomised to one of two treatment arms (atenolol and hydrochlorthiazide) in PEAR, or underwent sequential monotherapy with metoprolol followed by chlorthalidone (PEAR 2). LC/MSMS metabolomics of baseline plasma samples were performed by Metabolon Inc. Blood pressure response (BPR) was calculated as the difference between blood pressure during and before treatment. Metabolite BPR association was tested by linear regression adjusted for age, sex, ethnicity, BMI, study site and baseline BP. Family Wise Error Rate (FWER) was controlled conservatively using Holm correction. Results: 2-hydroxyglutarate (2-HG) strongly associated with diastolic BPR to hydrochlorothiazide (Holm p-value = 0.00045). Diastolic and systolic BP were both predicted to rise 2.2 mmHg per standard deviation increase in pre-treatment 2-HG quantile normalised level. For systolic BPR the effect was nominally significant. No other drug associated with 2-HG. The most significant BPR ethnicity by metabolite interaction was for vanillylmandelate (VMA) and diastolic BPR to atenolol (Holm p-value = 0.047). It predicts an extra 7.1 mmHg diastolic BP drop in whites compared to blacks, per standard deviation increase in pre-treatment VMA quantile normalised level. The systolic BPR interaction was almost as significant. Conclusions: Systematic metabolomic analyses identified 2-hydroxyglutarate as a predictor of hydrochlorothiazide response and ethnicity specific effect of VMA on atenolol response.